2000
DOI: 10.1179/146580100101541058
|View full text |Cite
|
Sign up to set email alerts
|

Short glass fibre reinforcedpoly(butylene terephthalate) Part 1 –Microstructural characterisation and kinetics of moisture absorption

Abstract: The kinetics of moisture absorption have been studied by immersing poly-( butylene terephthalate) (PBT) and its short glass fibre reinforced composites (SGF-PBT) in water at 30, 60, and 90°C. A single free phase model of absorption was applied to the kinetics data and the diffusion coefficient or diffusivity D was evaluated. The value of D was found to be strongly dependent on the water immersion temperatures and to a limited extent on the volume fraction of fibres. The incorporation of fibres resulted in a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Variations in temperature and moisture are always encountered by these materials in service. Their combined effect, known as hydrothermal aging, can be more damaging to the mechanical properties of the composites than to either component alone 1. Some efforts have been focused on the hydrothermal behavior of thermoplastic composites 2–5.…”
Section: Introductionmentioning
confidence: 99%
“…Variations in temperature and moisture are always encountered by these materials in service. Their combined effect, known as hydrothermal aging, can be more damaging to the mechanical properties of the composites than to either component alone 1. Some efforts have been focused on the hydrothermal behavior of thermoplastic composites 2–5.…”
Section: Introductionmentioning
confidence: 99%
“…Among the results found in the literature, Bastioli et al [ 48 ], studied the water uptake of fiber-free PBT at 37 °C and identified a coefficient of diffusion of 4.40 × and an infinite mass of 0.65%, which is close to the results obtained for PBT at 35 °C. Ishak et al [ 32 ], at 30 °C, identified a coefficient of diffusion of 1.90 × for fiber-free PBT and 1.00 × for PBT-GF30. Closer to the highest temperature studied in the present paper, at 100 °C, Ishak et al [ 21 ] identified an infinite mass of 0.71% and a coefficient of diffusion of 4.05 × for a content of fibers close to 30% (at about 28.5%).…”
Section: Resultsmentioning
confidence: 99%
“…Ishak et al [ 32 ] studied the behavior of short fiber reinforced PBT immersed in water at 30, 60 and 90 °C for fiber contents between 0 and 18% in volume. For high temperature (90 °C), the toughness of the material decreases significantly.…”
Section: Introductionmentioning
confidence: 99%
“…The water ingress behavior of materials is not described by a single universal rule. However, in the majority of the cases, the Fick’s law can be used to fit the empirical results [ 8 , 9 , 10 , 11 , 12 ]. This law is defined by the coefficient of diffusion, D , which is related to the diffusion rate, and the water uptake at saturation, .…”
Section: Introductionmentioning
confidence: 99%